Challenges and Learning Experiences of Physical Education (BPED) Students in Higher Education Institution (HEI) in Writing Research in the Time of Pandemic - D. Aquino, John Michael; G. Catapang, Rosario (ASEAN Journal of Education, 2023)
This study researched the challenges and learning experiences of BPED students at HEI when completing research for their undergraduate degree during the Covid-19 pandemic as the foundation for developing an innovation plan to assist future researchers in drafting their studies. The researchers used qualitative research design employing narrative inquiry which included in-depth explorations of the respondents' lived experiences and utilized semantic thematic analysis; coding, and themes. Focus group discussion was used to collect data in 7 BPED students which was chosen purposively. The results revealed that the challenges experienced were lack of teachers’ knowledge, availability of resources, effects of pandemic, teachers’ attitude and student’s behavior. In contrast, the students learning experiences included learning the process of writing research, good qualities of writers, positive attitude of research writers, and presence of a support system. Research is vital in education since it is continually developing; thus, ideas and solutions to meet the changes must be updated to best suit the current educational atmosphere for both faculty and students. This study may adopt a quantitative research design in the future to explore the challenges and learning experiences of BPED students. Other colleges or programs may likewise investigate their writing research experiences. Future researchers may look at other characteristics to have a better grasp of college students' writing research.